O processo organizativo da greve no contexto de uma biblioteca universitária brasileira - Lôbo, Perla Rodrigues (2016)
In a dynamic context of a strike people live in continuous interaction, they understand and build meanings and senses to daily activities and turn organizations into learning and knowledge construction spaces. Thus, by revealing practices performed in thi